(Mis-)matching in Germany : an analysis on the basis of empleyee's formal qualifications and skills - Rohrbach-Schmidt, Daniela [Verfasser]; Tiemann, Michael [Verfasser] (My University, 2011)
"People are not always employed in jobs that perfectly match their skills and abilities. Research on the question as to what constitutes a good match is usually based on the empirical correspondence between employees' formal qualifications and the formal qualification requirements of their jobs, but so far no up-to-date and in-depth information exists on the incidence of skill-based mismatching in Germany. This article uses the BIBB/BAuA Employment Survey 2006, which yields rich information fitting the job-requirement approach, to provide up-to-date and in-depth figures on the incidence of formal and skill-based mismatching in Germany. Moreover, it studies the extent to which mismatching varies with employees' socio-demographic and qualification characteristics and with job tasks." (Autorenreferat, BIBB-Doku)
Keywords: G 1.3.1 Bildungsangebot & -nachfrage; G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; G 1.2.2.3 Beschäftigungsformen; Mismatch; Berufliche Qualifikation; Adäquate Beschäftigung; Tätigkeitsmerkmal; Erwerbstätiger; Befragung